Clinical presentation of PTEN mutations in childhood in the absence of family history of Cowden syndrome. (March 2015) - Busa, T.; Milh, M.; Degardin, N.; Girard, N.; Sigaudy, S.; Longy, M.; Olshchwang, S.; Sobol, H.; Chabrol, B.; Philip, N.
Abstract Background PTEN gene (MIM 601628) is a tumor suppressor gene implicated in PTEN hamartoma tumor syndromes (PHTS) including Cowden syndrome, Bannayan–Riley–Ruvalcaba syndrome, and Proteus-like syndrome. Bannayan–Riley–Ruvalcaba syndrome is considered as the pediatric form of PHTS. More recently, children presenting autism spectrum disorders with macrocephaly (ASD-M) have been reported. Methods We report clinical data from seven patients diagnosed in childhood with a PTEN germline mutation, excluding cases of familial Cowden syndrome. Results This study underlines the variability of phenotype associated with PTEN mutations diagnosed at pediatric age. Most of the patients did not fulfill usual criteria of Bannayan–Riley–Ruvalcaba syndrome or ASD-M. Conclusion PTEN testing should be considered in any child presenting with severe macrocephaly (>+4SD) and another feature of PHTS.